The Relationship between Radiotherapy and Cognitive Impairment in Brain Tumor Patients : A Systematic Review - Ahmad Dalma Haidar; Arda Fatkhul Khoiriyah (The International Journal of Medical Science and Health Research, 2026)
Introduction: Radiotherapy (RT) is a cornerstone in treating brain tumors but is associated with potential cognitive decline. The relationship between RT and cognitive impairment is complex, influenced by tumor type, RT modality, and patient-specific factors. Methods: This systematic review synthesized data from 80 included studies encompassing a broad range of designs, from randomized controlled trials, etc. We extracted data on patient populations, RT details (whole-brain radiotherapy [WBRT], stereotactic radiosurgery [SRS], proton therapy), cognitive assessment methods, outcomes, dose-response relationships, underlying mechanisms, risk factors, and prevention strategies. Results: WBRT produced the most severe cognitive decline, with 91.7% of patients experiencing deterioration at 3 months compared to 63.5% with SRS alone (P. Brown et al., 2016). SRS-based approaches resulted in substantially less cognitive morbidity. Hippocampal-avoidance (HA)-WBRT significantly reduced cognitive failure (adjusted HR=0.74, p=0.016) (Crockett & Simões, 2023). Mean brain dose inversely predicted cognitive trajectories in IDH-mutant glioma (Jaspers et al., 2024). Key mechanisms include vascular injury, white matter damage, neuroinflammation, and oxidative stress. Risk factors include older age, low cognitive reserve, and pre-existing leukoencephalopathy. Discussion: The findings reveal a consistent hierarchy of cognitive toxicity: WBRT > SRS > focal/partial brain RT. A central tension exists between maximizing tumor control (achieved by WBRT) and preserving cognition (achieved by SRS and hippocampal sparing). Distinguishing tumor-related from treatment-related cognitive effects remains a key challenge, as baseline impairment is highly prevalent. Dose-response relationships are structure-specific, implicating the hippocampus, entorhinal cortex, thalamus, and white matter tracts. Neuroprotective strategies, including memantine and HA-WBRT, show benefit, while donepezil offers modest improvements. Conclusion: Modern RT protocols should prioritize cognitive preservation through appropriate modality selection (SRS alone for 1-3 metastases), hippocampal avoidance, and minimizing mean brain dose. Future research should focus on integrating cognitive endpoints into clinical trial design and validating dosimetric constraints for distributed brain structures.